Analysis of Public Perception of the Implementation of Minister of Home Affairs Regulation Number 72 of 2022: A Quantitative Study on Digital Population Identity in Pontianak City - Riyoldi; Entang Adhy Muhtar; Nina Karlina (Journal of Law, Politic and Humanities, 2025)
The Indonesian government, through Minister of Home Affairs Regulation No. 72 of 2022, introduced the Digital Population Identity (IKD) application as a step toward digital transformation in administrative services. This study aims to analyze public acceptance of the IKD application in Pontianak City using the Technology Acceptance Model (TAM) framework, focusing on the dimensions of Perceived Usefulness (PU) and Perceived Ease of Use (PEU). A survey of 467 respondents revealed that while the application is acknowledged as beneficial and relatively easy to use, a significant proportion of neutral responses in both dimensions indicates a gap between user expectations and experiences. Privacy concerns and trust in data security emerged as key challenges to technology adoption. By integrating risk and trust theories into TAM, this study finds that government transparency, data security enhancement, and digital literacy education are essential elements for building public trust. The study recommends optimizing application features, improving interface design, developing segmented communication strategies, and strengthening public outreach to establish an inclusive and reliable digital ecosystem for administrative services.